Oceanic response to typhoons in the Northwest Pacific using Aquarius and SMAP data (2011–2020) - Park, Kyung-Ae; Park, Jae-Jin; Tang, Wenqing (Frontiers in Marine Science, 2023)
Typhoons, such as tropical cyclones, can produce a variety of ocean responses through drastic changes in atmospheric and oceanic environments. However, the uncertainty in satellite salinity data increases during the passage of a typhoon and may limit its potential application. To investigate whether the satellite salinity data can explain oceanic responses to typhoons in the Northwest Pacific, we validated the satellite salinity using Argo float data for the past decade (2011–2020). The Soil Moisture Active Passive (SMAP) and Aquarius salinity were relatively accurate in subtropical regions at low latitudes under high sea surface temperature conditions in summer. This demonstrates the validity of the satellite salinity data in typhoon studies. We analyzed the oceanic responses to 20 representative typhoons over the past decade. Both the Aquarius and SMAP satellites observed a decrease in the SSS on the left side of the typhoon in contrast to the high salinity on the right side of the typhoon. The locations of SSS freshening coincided with those of higher precipitation to the left of the typhoon centers. We also observed that the higher the precipitation rate, the lower the satellite salinity. The ratio of the salinity freshening to the precipitation rate was significant at approximately –0.0401 psu/mm/h. Changes in the vertical profiles of the Argo data supported this partial freshening of salinity as well as the characteristic surface cooling and deepening of the mixed layer after the passage of the typhoon. We further demonstrated that the atmospheric environments in a rotated coordinate system along the typhoon paths showed clear salinity freshening in the forward and slightly left sides of the typhoon center. The spatial distinction of the wind and precipitation fields along the typhoon paths induced the characteristic synoptic response of salinity prior to the arrival of each typhoon. Our results provide reasonable observational evidence of oceanic responses to typhoons in the Northwest Pacific and contribute to the understanding of atmospheric and oceanic processes related to tropical storms.